Mandibular quality assessment in women aged 40-60 years using mandibular cortical index and antegonial index on panoramic radiographs - Sarifah, Norlaila; Hamdani, Riky; Nurrahman, Tri (Jurnal Radiologi Dentomaksilofasial Indonesia (JRDI); Vol 6 No 3 (2022): Jurnal Radiologi Dentomaksilofasial Indonesia (JRDI), 2022)
Objectives: This study aimed to describe the cortical quality of the mandible in women aged 40-60 years by analyzing the mandibular cortical index and antegonial index on panoramic radiographs. Materials and Methods: This study was a cross-sectional analytic descriptive study, population, and sample using secondary data on panoramic radiographs of women aged 40-60. The descriptive analysis technique used in this study was the average value (mean), standard deviation, and thickness of the mandibular cortex in radiographs of female patients aged 40-60 years. Results: This study observed variations in mandibular cortical bone quality on panoramic radiographs, with increasing age, bone quality tends to decrease, and there is an effect of gender involvement. Women tend to have lower bone quality, one of which is due to hormonal factors.   This study observed variations in mandibular cortical bone quality on panoramic radiographs, with increasing age, bone quality tends to decrease, and there is an effect of gender involvement. Women tend to have lower bone quality, one of which is due to hormonal factors.  The age group at risk of osteoporosis had the lowest mandibular cortex width value in the age group of 51-60 years. Conclusion: This study produced a variety of panoramic radiographs of the mandibular cortical bone quality. The value of the width of the mandibular cortex gradually decreases with age. The value of mandibular cortex width is higher in the younger generation.